COMPARATIVE ANALYSIS OF THE DEFINITIONS OF POPULISM AND CYNICISM AS “NARROW” IDEOLOGIES - BABAJANYAN, LEVON (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The article considers populism and cynicism as “narrow” types of ideology. The “broad” ideologies, such as liberalism, socialism, nationalism, and so on, are based on descriptive and normative ideas, while “narrow” ideologies are based only on descriptive ideas. As a result of the analysis of some ideological concepts of populism and cynicism, a number of common and different features were identified among the analyzed “narrow” ideologies.